2015
DOI: 10.5539/ijc.v7n1p62
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Triterpenoids of Ganoderma lucidum with Aspartic Protease Enzymes for Discovering HIV-1 and Plasmepsin Inhibitors

Abstract: Rapid resistance development of HIV-1 and Plasmodium falciparum parasite requires discovery of more potent new drugs. Aspartic protease enzymes expressed by HIV-1 and P. falciparum could be used as important drug targets. The catalytic site is located at the bottom of a cleft in the enzyme surface and consists of triad Asp25, Thr26, Gly27. Important aspartic acids are Asp32 and Asp215. Aspartic proteases are inhibited by pepstatin-A, a naturally occurring peptide containing two statins, which replace the amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…They found that those compounds had strong inhibitory activity against HIV-1 proteases. Recently, Kang, Mutakin [29] also indicated that ganoderic acid B possessed the highest inhibiting activity to HIV-protease of four tested triterpenoids. In addition, Zhang, Ip [30] reported the extractive of G. lucidum could inhibit HIV-1 reverse transcriptase.…”
Section: Anti-hiv Activitymentioning
confidence: 94%
“…They found that those compounds had strong inhibitory activity against HIV-1 proteases. Recently, Kang, Mutakin [29] also indicated that ganoderic acid B possessed the highest inhibiting activity to HIV-protease of four tested triterpenoids. In addition, Zhang, Ip [30] reported the extractive of G. lucidum could inhibit HIV-1 reverse transcriptase.…”
Section: Anti-hiv Activitymentioning
confidence: 94%
“…Ganoderiol F (142), ganodermanontriol (322), ganolucidic acid A (38), ganolucidic acid B (39), ganoderic acid GS-2 (84), 15a-acetoxy-3a-hydroxylanosta-8,24-dien-26-oic acid (445), colossolactone V (297) and ganoderiol F (142) have anti-HIV-1 activity. [102][103][104][105] The hydroxyl groups at positions C-3, C-24 and C-25 in lanostane triterpenoids are the necessary active groups for anti-HIV-1 virus. 106 Among them, compounds 84 and 142 inhibit human immunodeciency virus-1 protease with IC 50 values of 20-40 mM.…”
Section: Antiviral Activitymentioning
confidence: 99%
“…The docking results of Ganomycin 1 and Ganomycin 2 with HIV 1 protease show significant inhibitory action of these compounds, indicating the possibility that they can be used in the antiretroviral therapy as potent drugs. A triterpenoid isolated from the stem of Ganoderma sinense showed higher affinity towards HIV-1 protease with binding energy of -11.4kcal/mol using AutoDock 4.2 software 13 . Similar effect of ganoderic acid B was studied by Akbar and Yam on HIV 1 protease and indicated a huge potential for HIV treatment 14 .…”
Section: Fig 3: Docking Interactions Of Receptor Hiv 1 Protease a Wmentioning
confidence: 99%